The relative value relevance of book values, operating cash flows, EVA and earnings: A South African perspective - Muzhingi, Taurai (Department of Finance and Tax, 2019)
Most investors would want to know what is included in the price of a share and how far accounting data explain the share price. This study uses the most common measures of financial performance to measure what is explained by the share price. Most analyst briefings use these financial performance measures: book value per share, cash flow per share, earnings per share and most recently the market performance measure, the economic value added (EVA) in the share valuations. The objective of the study is to examine the relationship between the above measures of financial performance as presented in financial statements and the share prices and share returns. If there is a relationship, which measure is most closely related to both share prices and share returns? The study uses data obtained from a balanced sample of 87 companies listed on the Johannesburg Stock Exchange (JSE) during the ten-year period (2005-2014). Both the price and the returns models were used to analyse this financial data to find out which accounting measure has the greatest explanatory power on the share prices and share returns (measured by the R-squared or R 2metric). For the price model, share prices 3 months after the financial yearend were used to allow for the release of financial information. Using the price model, earnings have the highest overall R2 at 56.4%, with book values at 18.4%, EVA at 2.18% and lastly operating cash flows at 1.18%. This effectively means that earnings per share is more value relevant in determining firm value than either book value of equity, EVA and operating cash flows, respectively. Using incremental value relevance, equity book values and earnings explain 65% of the share prices. However, changes in EVA deflated by price have the greatest explanatory power (R 2 at 30%) using the returns model and none of the other measures(earnings and operating cash flows) have a significant relationship with share returns. Overall the results show that both accounting based (book value of equity and earnings) and market based measures (EVA) are value relevant in determining firm value. The results also show that a consideration of more than one variable in determining firm value is more informative than considering each variable separately. EVA should also be used in determining value as it has shown that it explains some of the share prices and returns.